Effectiveness and safety of high dose oral ibuprofen versus standard dose for treatment of preterm infants with patent ductus arteriosus - Yaowaret Mekkhayai (2018)
© 2015 International Journal of Pharmacy and Pharmaceutical Science. All Rights Reserved. Objective: The objective of this research compares effectiveness and safety of high-dose oral ibuprofen and standard dose for treatment symptomatic PDA. Methods: A retrospective cohort study was carried out in 126 preterm infants with patent ductus arteriosus (PDA) who received oral ibuprofen and hospitalized in neonatal intensive care unit and sick newborn ward during January 2010-December 2014, preterm infants with PDA was assigned to high dose (10-10-10 mg/kg/day) oral ibuprofen group and standard dose group (10-5-5 mg/kg/day), 63 patients within in each group. Results: Baseline characteristics were no significant difference between two groups. The closure rate of the ductus arteriosus of the high dose group was significantly higher (82.5%) than in standard dose group (66.7%) (p=0.04). So, lower rate of re-open and PDA ligation. However, ductus arteriosus closure rate at discharge was not significantly different. There was no significant difference between two groups in adverse drug reaction. Conclusion: The results obtained for this study show the high dose of oral ibuprofen is more effectiveness than the standard dose for closing PDA in preterm infants without increasing the adverse drug reaction rate.